2012
DOI: 10.1002/pi.4418
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity and photovoltaic properties of polyaniline immobilized onto metallurgical porous silicon powder

Abstract: Photoactive composites comprising polyaniline and metallurgical silicon powder were prepared by an in situ two‐step procedure (pSi‐PANI). Their structures were elucidated by electronic and infrared spectroscopy and powder X‐ray diffraction (P‐XRD) techniques. The P‐XRD revealed that the acid‐doped green composites (pSi‐PANI·HCl and pSi‐PANI·HF) acquire a two‐dimensional crystalline array structure featuring nanosheet morphology. The photoconductivity and photovoltaic (PV) properties of these composites were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…In addition, owing to its high theoretical capacity, it has been recognized as the most attractive and promising anode material for lithiumion batteries, (more than 11 times theoretical capacity of graphite) [13,14]. It has also been reported by Arafa et al [15] that polyaniline immobilized onto metallurgical pSimPs is highly promising for the development of an inexpensive and flexible photovoltaic system. These types of porous micro-particles were prepared via numerous methods, such as electrochemical etching [16,17] (the most familiar method), stain-etching in a hydrofluoric acid-based solution [18,19] and by a metal-assisted chemical etching method [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, owing to its high theoretical capacity, it has been recognized as the most attractive and promising anode material for lithiumion batteries, (more than 11 times theoretical capacity of graphite) [13,14]. It has also been reported by Arafa et al [15] that polyaniline immobilized onto metallurgical pSimPs is highly promising for the development of an inexpensive and flexible photovoltaic system. These types of porous micro-particles were prepared via numerous methods, such as electrochemical etching [16,17] (the most familiar method), stain-etching in a hydrofluoric acid-based solution [18,19] and by a metal-assisted chemical etching method [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the few papers, it has been suggested that polyaniline can produced photoelectric effect on inert electrodes [94][95][96][97][98][99]. But, up to now the influence of light on the corrosion of mild steel with the electroconducting polymer coatings has not been investigated.…”
Section: The Influence Of Light On Corrosion Behavior Of Polyaniline mentioning
confidence: 99%